Sistem Monitoring pH dan Kelembaban Tanah Berbasis IoT untuk Optimasi Pertumbuhan Tanaman Terong: Tanaman Terong Berbasis IoT - Sunanto, Sunanto; mitra unik; Desti Mualfah (Universitas Muhammadiyah Riau, 2024)
The growth of eggplant plants is greatly influenced by environmental conditions, especially pH and soil moisture. These parameters need to be monitored regularly to ensure optimal conditions for the plant. In this study, an Internet of Things (IoT)-based monitoring system was developed to monitor soil pH and moisture in real-time. The system uses pH sensors and humidity sensors connected to microcontrollers and combined with IoT connectivity to send data to a cloud platform. The data collected can be accessed through a mobile application, allowing farmers or land managers to monitor soil conditions remotely. The results of the implementation show that the system is able to provide accurate and real-time information on soil pH and moisture, as well as provide notifications when these parameters are outside the optimal range. With this system, it is hoped that farmers can take corrective action quickly to maintain the condition of